The Relationship between Adherence to Antihypertensive Medication and Microalbumin Levels in Hypertension Prolanis Patients - Arief Adi Saputro; Anisa Sholikhati; Yunita Rusidah (Universitas Prima Indonesia, 2025)
Hypertension is one of the main health problems faced by people throughout the world, including in Indonesia. Uncontrolled hypertension can cause various complications such as heart disease, stroke and kidney damage. Microalbuminuria, namely the presence of small amounts of albumin in the urine, is an early indicator of kidney damage. In hypertensive patients, microalbuminuria can be an early sign of hypertensive nephropathy, which is a serious complication of high blood pressure. Compliance with taking medication affects blood pressure control. This study aims to evaluate the relationship between adherence to antihypertensive medication and microalbumin levels in hypertension prolanis patients. This research is observational analytic with a cross sectional approach. Data was obtained prospectively in the period July-August 2024 with a sample size of 33 respondents. Medication adherence was taken using a questionnaire, and data on microalbuminuria levels was obtained through medical record data. Next, the results were subjected to a chi-square statistical correlation test. Microalbumin levels and medication adherence blood pressure lowering medication, obtained a value of p = 0.0 (p < 0.05) which indicates that statistically there is a significant relationship between microalbumin levels and compliance of taking blood pressure lowering medication. The frequency distribution of hypertensive sufferers with high microalbumin levels, namely ≥ 30 mg/dL, shows a result of 51.6% (17 patients).